Mass spectrometric and thermodynamic studies reveal the role of water molecules in complexes formed between SH2 domains and tyrosyl phosphopeptides. - Chung, E; Henriques, D; Renzoni, D; Zvelebil, M; Bradshaw, J; Waksman, G; Robinson, C; Ladbury, J (1998)
BACKGROUND: SH2 domains have a fundamental role in signal transduction. These domains interact with proteins containing phosphorylated tyrosine residues and, in doing so, mediate the interactions of proteins involved in tyrosine kinase signalling. The issue of specificity in SH2 domain interactions is therefore of great interest in terms of understanding tyrosine kinase signal-transduction pathways and in the discovery of drugs to inhibit them. Water molecules are found at the interfaces of many complexes, however, to date little attention has been paid to their role in dictating specificity. RESULTS: Here we use a combination of nanoflow electrospray ionization mass spectrometry (ESI-MS), isothermal titration calorimetry and structural data to investigate the effect of water molecules in complexes formed between the SH2 domain of tyrosine kinase Src and tyrosyl phosphopeptides. Binding studies have been performed using a series of different peptides that were selected to allow changes in the water content at the complex interface and demonstrate changes in specificity. ESI-MS enables quantification of the number of water molecules that interact with a higher affinity than those generally found solvating the biomolecular complex. CONCLUSIONS: Comparing the interactions of different peptides, we show that an intricate network of water molecules have a key role in dictating specificity. The use of mass spectrometry to quantify tightly bound water molecules may prove of general use in structural biology, where an independent determination of the water molecules associated with a structure would be advantageous. Furthermore, the ability to assess whether given water molecules are important in high-affinity binding could make this method a precious tool in drug design.